2015
DOI: 10.3151/jact.13.214
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Humidity Fields in Concrete: Experimental Validation and Parameter Estimation

Abstract: The moisture content in concrete structures has an important influence in their behavior and performance. Several validated numerical approaches adopt the governing equation for relative humidity fields proposed in Model Code 1990/2010. Nevertheless there is no integrative study which addresses the choice of parameters for the simulation of the humidity diffusion phenomenon, particularly in concern to the range of parameters forwarded by Model Code 1990/2010. A software based on a Finite Difference Method Algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
(110 reference statements)
0
4
0
4
Order By: Relevance
“…The decoupled humidity field for 1D using FDM is previously presented in Oliveira et al [45]. For carbon dioxide field, the mathematical implementation is similar, thus for the sack of brevity, the implementation of both fields are herein omitted, further details may be seen in literature [45].…”
Section: Implementation Of Multi-physics Modelling: a Brief Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decoupled humidity field for 1D using FDM is previously presented in Oliveira et al [45]. For carbon dioxide field, the mathematical implementation is similar, thus for the sack of brevity, the implementation of both fields are herein omitted, further details may be seen in literature [45].…”
Section: Implementation Of Multi-physics Modelling: a Brief Discussionmentioning
confidence: 99%
“…For brevity and due to the similarity with the 1D implementation, the 2D and axisymmetric implementations are not presented herein, more details can be seen in Oliveira [10]. The chosen notation for reaction field R is the same adopted in Oliveira et al [45], where "i" represents the node, and "n" reads as the time step [10].…”
Section: Implementation Of Multi-physics Modelling: a Brief Discussionmentioning
confidence: 99%
“…To explore the influence of different curing effects on the humidity field, three calculation conditions (60, 80, and 100%) are defined based on the varying environmental humidity. According to the research results obtained by Oliveira et al [25], the surface factor f boundary is approximately linear with D 1 , as shown in equation (29):…”
Section: Calculation Modelmentioning
confidence: 94%
“…e humidity transfer rate at the concrete surface is related to ambient humidity, wind speed, and temperature. It can be calculated using equation ( 18) [25]:…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…Para uma análise detalhada do campo de umidade, torna-se essencial o conhecimento do perfil de umidade ao longo do tempo [22], bem como a redução pela auto-dissecação do material, que corresponde ao fenômeno associado a redução da umidade pelo consumo próprio do material [2,7,22]. A estratégia adotada neste trabalho pretende investigar a difusão de umidade na argamassa de cal aérea nas idades inicias, ou seja.…”
Section: Introductionunclassified